Master Merrythought's Balladeering: A Memetic Approach to Ballad Singing in The Knight of the Burning Pestle - Peterson, Noah Gene (Early Theatre)

(untitled) (McMaster University Library Press / Becker Associates, 2026)
This paper argues that we can understand the many ballad and song references within The Knight of the Burning Pestle as memes, cultural referents which allow for several layers of meaning to be added onto the play. The paper discusses the ballads and songs as memes operating individually within the play and as “memeplexes” created by the complex and overlapping interactions of songs as they appear in multiple plays or other types of literature.